2007
DOI: 10.1021/ja072841c
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of the Spectroscopy versus Crystallography Issue for NO Intermediates of Nitrite Reductase from Rhodobacter sphaeroides

Abstract: Copper nitrite reductase (NiR) is a homotrimeric enzyme, containing a T1 copper site, which transfers electrons to the T2 catalytic site, where nitrite is reduced by one electron to nitric oxide (NO 2 − + 2H + + e − → NO + H 2 O). 1-3 Recently a side-on bound copper nitrosyl complex of NiR has been crystallized by reacting the reduced enzyme with excess NO. 4 Based on the EPR spectrum of the species generated by the reaction of reduced NiR with saturated NO in solution, it has been assigned as an η 2 -NO − Cu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
70
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(73 citation statements)
references
References 14 publications
3
70
0
Order By: Relevance
“…A conundrum remained: Which Cu-NO species is produced in the enzymatic cycle (VI)? Whereas side-on NO is stabilized in crystal structures (22,23,25), spectroscopic and computational studies indicate that end-on NO is a physiological intermediate (37)(38)(39)(40). Although visualization of an end-on NO species with short lifetime has been difficult, time-resolved SFX may enable it (60,61).…”
mentioning
confidence: 99%
“…A conundrum remained: Which Cu-NO species is produced in the enzymatic cycle (VI)? Whereas side-on NO is stabilized in crystal structures (22,23,25), spectroscopic and computational studies indicate that end-on NO is a physiological intermediate (37)(38)(39)(40). Although visualization of an end-on NO species with short lifetime has been difficult, time-resolved SFX may enable it (60,61).…”
mentioning
confidence: 99%
“…xylosoxidans (NCIMB 11015, AxNiR) was overexpressed in Escherichia coli BL21(DE3) cells, and the purification was similar to the method described previously (42,43) (see supplemental material for detailed description). AxNiR concentrations were determined using an extinction coefficient of 4 Very recently spectroscopic and computational methods have shown that ET from the T1 to the T2Cu sites in the green copper enzyme RsNiR (Rhodobacter sphaeroides) requires the initial proton transfer from the Asp residue in the active site pocket to nitrite thereby triggering the reductive cleavage of the substrate (40,41 ⑀ 595 ϭ 6.3 mM Ϫ1 cm Ϫ1 (9,18). The AxNiR enzyme lacking the copper atom in the T2Cu center (T2DNiR) was expressed and purified in the same way as AxNiR except that the dialysis steps into CuSO 4 were omitted (27,42,44).…”
Section: Methodsmentioning
confidence: 99%
“…The relevance of these active site residues, however, as well as the timing of the two protonation steps is still a matter of debate (35,40,41). 4 There are no experimental studies that have been aimed at directly examining the kinetic coupling of PT and ET steps in AxNiR.…”
mentioning
confidence: 99%
“…This interpretation was based on EPR simulations assuming typical g-and A-values for a T2 site plus hyperfine coupling to four N-nuclei at g ⊥ , three from the coordinating histidines and one from the NO, and on X-ray data which showed a side-on NO coordinated to Cu [41]. In contrast, other authors, on the basis of EPR, ENDOR (Electron-Nuclear Double Resonance), and DFT (Density Functional Theory) calculations in R. sphaeroides NiR [42,43], concluded that the species generated in solution of ascorbate-reduced Nir with excess NO corresponds to a Cu II -NO 2 − species.…”
Section: Epr Characterization Of the Copper Centersmentioning
confidence: 97%